Rawls and private law - DOI: 10.5935/2448-0517.20190004 - Zanitelli, Leandro Martins (Juris Poiesis - Qualis A3, 2019)
The paper assesses the place of private law in John Rawls"s theory of justice. A considerable part of the literature on that issue tries to ascertain whether private law belongs to the basic structure of society, the set of major social institutions to which Rawls"s principles of justice apply. Here it is argued that more important than determining the basic structure"s scope is to clarify the role that private law, once conceived as part of that structure, plays in Rawlsian justice. Such role is, in some sense, secondary, which explains why Rawls sometimes suggests, against the most usual broad definition of basic structure, that private law is alien to his principles of justice. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->